Avances Tecnológicos para la autorreparación de grietas para materiales de Construcción de Pavimentos Rígidos (2021)
This project was carried out due to the lack of studies in Spanish, on the subject of selfrepairing technologies, additionally with the current state of the Colombian roads, due to cracking caused by external and internal factors, they present a short useful life; For this reason, alternatives are sought to increase its durability, mitigate its cracking and maintain or increase its mechanical properties. In this way, alternatives using self-repairing agents such as autogenous or autonomous are proposed, and some materials implemented for crack sealing and increasing their durability are also presented. This allowed to establish their approximate costs adding their advantages and disadvantages, concluding that, it is a topic which should be further investigated.